An introduction to epilepsy - Schachter, Steven (Henry Stewart Talks, 2011)
Principles of accurate diagnosis, Definitions and epidemiology, Seizures that are not epilepsy, Disorders that mimic seizures, The underlining cause of seizure, Patients' medical history, Neurological examination & Lab evaluation, Principles of AED therapy, Factors that help determine type of treatment, Elderly, Comprehensive management: non-AED issues, Strategies to enhance outcomes, Patient education resources, Epilepsy-related issues, Driving, Referral to epileptologist